#TITLE_ALTERNATIVE# - RISDIANTO (NIM 23005004), HENDRO
Pulp from kraft process was bleached in order to obtain white paper. The most common method to bleach pulp is chemical method, employing several phases of reactions using chlorine and natrium hydroxides. This bleaching process produces detrimental pollutant, detected as Adsorbable Organic Halide (AOX). There are several ways have been proposed to reduce the negative impacts of chemical bleaching process, Elemental Chlorine Free (ECF) system and Totally Chlorine Free (TCF) system. ECF system using chlordioxide compounds, whereas TCF system using non chlorine compounds for pulp bleaching. One of enviro-friendly pulp bleaching process is the application of lignindegrading enzymes to reduce or eliminate the use of chlorine compound. Lignindegrading enzyme used in many pulp and paper industries is laccase. This research was focusing on the development of method to produce laccase for pulp bleaching process. The research was divided into four phases of studies i.e.: (a). selection of fungi species for laccase production, (b). selection of support medium, (c). laccase production in a modified temporary immersion bioreactor and (d). utilisation of laccase crude enzyme in pulp bleaching process. Fungi selection study suggesting that Marasmius sp. exhibit a better performance in term of growth and delignification capability, compared to Trametes hirsuta. The Marasmius sp. showed a higher average colony growth rates (20.68 mm/day) compared to that of Trametes hirsuta (14.17 mm/day). The colony radial growth rates Marasmius sp. (25.05 mm/day) was also higher compared to that of Trametes hirsuta (17.45 mm/day). In addition to this, the Marasmius sp. exhibits a higher specific growth rates (2.06/day) compared to that of Trametes hirsuta (1.33/day). Further study on lignin degradation capability indicates that, eventhough both Marasmius sp. and Trametes hirsuta produced extracellular enzymes, only Marasmius sp. exhibited lignin degradation activity during 60 day incubation of fungi in lignin containing agar plate. Based on this study, Marasmius sp. was selected for future studies. Study on growth supporting medium was carried out to select the best material to support the growth of Marasmius sp. The experiment was carried out on synthetic medium (bioball and scouring pad) and natural medium (luffa sponges). Fungi growth on the support media was determined based on visual observation. The study showed that Marasmius sp. grows best on luffa sponges, thus luffa sponges was selected as supporting medium for Marasmius sp. Experiments with cultivation of immobilised Marasmius sp. in a modified temporary immersion bioreactor were conducted to study the effect of variations of immersion periods in the production of laccase. The immersion periods applied in this study were 15 minutes, 12 hours and 24 hours. Results showed that immersion period of 12 hours exhibited the highest maximum laccase activity. Maximum level of laccase attained from culture with 12 hours immersion period was 457.6 U/l, higher compared to that attained with 15 minutes (348.4 U/l) and 24 hours (281.9 U/l) immersion period. However, culture with 12 hours immersion period did not show the highest activity. Culture with 15 minutes immersion period exhibited the highest activity (348.4 U/l/day), followed by culture with 24 hours immersion period (281.9 U/l/day) and culture with 12 hours immersion period (152.5 U/l/day). Further study on second cycle of laccase activitiy shows that all culture in the second cycle produce laccase with lower activity compared to that of first culture. The highest decreasing percentage of laccase activity on 2nd cycle occured during immersion period of 24 hours (80.66%) then followed with the 12 hours (64.30%) and 15 minutes (3.83%). The decreased in laccase activities possibly due to the production of other enzymes (most probably cellulase). Laccase activity can also be expressed as Unit per total protein (U/mg protein). The study showed that laccase activity in the 1st cycle of Marasmius sp. cultivation was higher compared to that produced in the 2nd cycle. Laccase activity in the 1st cycle for 12 hours immersion period was 7.46 U/(mg protein), the 15 minutes immersion period was of 3.49 U/(mg protein) and the 24 hours immersion period was 2.57 U/(mg protein). The decreasing of laccase activity in 2nd cycle for immersion period of 15 minutes, 12 hours and 24 hours were 58.08%, 82.24%, 91.68% respectively. Study on the application of laccase for pulp bleaching showed that pulp pretreatment with laccase crude enzymes gives a limited improvement on pulp brightness. The pretreatments have been conducted with and without addition of ABTS as mediator. Utilisation of crude enzymes by addition of ABTS mediator with enzyme exposure time 6 hours at temperature of 45°C increased brightness for 2.8 points. Pretreatment with similar conditions except that no ABTS was added demonstrated an increase in brightness for 0.7 point. It showed that addition of ABTS improved biobleaching process. Whereas pulp exposed to crude enzymes for 6 days at room temperature increased 5.3 points of pulp brightness. Analysis on the pulp fiber distribution before and after enzyme pretreatment showed that pretreatment using crude enzyme for 6 days lead to the reduction of fiber length, which is suggested due to the presence of cellulase. In contrast, a less reduction of fiber length reduction occured on addition of ABTS mediator. It is suggested that improvement of laccase production should be conducted to obtain a higher activity of laccase and reduce the production of cellulase.